Image Schema Analysis of Synonymy, Hyponymy, and Metonymy Relations - Taher , Marewan Dh.; Salih, Salah M. (Polytechnic Journal of Humanities and Social Sciences, 2024)
The rational of this study is to investigate the cognitive mechanisms involved in configuring sensory experience and encyclopaedic knowledge in the mental system through the analysis of synonymy, hyponymy, and metonymy relations. The aim is to characterise the conceptualization of synonymy, hyponymy, and metonymy relations in the conceptual structure by adopting Image Schema Theory (Johnson, 1987; Lokoff, 1987). Besides, it also aims at identifying the differences in embodying a pair of synonyms, a hyponym and superordinate, and two metonymic forms adopting image schema theory. These relations are analysed adopting a descriptive qualitative method using image schema theory. Thus, the motivation behind this study is to perceive how these relations are conceptualised and embodied in the mental structure of the speaker. The study concludes that these lexical sense relations can be conceptualised in the conceptual system by adopting image schema patterns. The adopted lexical sense relations can give rise to various image schematic patterns, so the structure of the sentence restricts the type of the pattern. In the analysis of metonymy relation, the image schema assigns an objective identification of the metonymic form. The most frequently used pattern is the FORCE image schema based on the analysed sentences. Keywords: Image Schema, Cognitive Semantics, Synonymy, Hyponymy, Metonymy.